2004
DOI: 10.1002/elsc.200400008
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Salvinia minima Baker to Tolerate and Accumulate As and Pb

Abstract: The use of Salvinia minima Baker for the removal of lead (Pb) and arsenic (As) from aqueous solutions was investigated. In a first approach, the effect of different concentrations of AsO 4 3± and Pb(II) on the growth and accumulation of these metals was studied. The plants tolerated concentrations of 20±40 lM Pb(II) and 200 lM of AsO 4 3± . Toxic effects occurred when 20 lM of Pb(II) and 100 lM AsO 4 3± were used. These effects included growth inhibition (decreased yield of biomass and frond area) as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…These values are similar to those we reported earlier for S. minima [14,20]. Furthermore, it is important to mention that these values remained high, considering that the initial lead concentrations used in this work are approximately four times higher than those tested earlier (an average of 11.4±0.4, versus an average of 3.5 mg/L).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These values are similar to those we reported earlier for S. minima [14,20]. Furthermore, it is important to mention that these values remained high, considering that the initial lead concentrations used in this work are approximately four times higher than those tested earlier (an average of 11.4±0.4, versus an average of 3.5 mg/L).…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting that such BCF values are a lot higher than those previously reported for Lemnaceaes. The BCFs for L. minor and A. pinnata were 138 and 140, respectively, for an initial lead concentration of 4 mg/L [14]. In another work [30], a BCF of 60 was reported for ''duckweed'' exposed to an initial lead concentration of 1.0 mg/L.…”
Section: Discussionmentioning
confidence: 87%
“…Other researchers also found that As uptake by plants increased, with increasing As concentration in the growth medium or soil (Ma et al, 2001;Hoffmann et al, 2004).…”
Section: As Absorption By Plant Partsmentioning
confidence: 80%
“…Though extensive literature is available highlighting the potential of several Salvinia species for accumulation/removal of various heavy metals including Ni, Cu, As, Pb, Cr, Zn from wastewaters (Sen and Mondal, 1990;Sen and Bhattacharya, 1994;Nigam et al, 1998;Nichols et al, 2000;Hoffman et al, 2004;Hadad et al, 2007), the physiological factors and regulatory mechanisms related to the greater potential of plants for tolerating high levels of heavy metals are not known. Moreover, the exact mechanism of damage to the photosynthetic apparatus whether electron transport or carbon assimilation when Salvinia natans is exposed to heavy metals has not been studied.…”
Section: Introductionmentioning
confidence: 99%